A scoping review of mobile apps for sleep management: User needs and design considerations - Al Mahmud, Abdullah; Wu, Jiahuan; Mubin, Omar (Frontiers in Psychiatry, 2022)
Sleep disorders are prevalent nowadays, leading to anxiety, depression, high blood pressure, and other health problems. Due to the proliferation of mobile devices and the development of communication technologies, mobile apps have become a popular way to deliver sleep disorder therapy or manage sleep. This scoping review aims to conduct a systematic investigation of mobile apps and technologies supporting sleep, including the essential functions of sleep apps, how they are used to improve sleep and the facilitators of and barriers to using apps among patients and other stakeholders. We searched articles (2010 to 2022) from Scopus, Web of Science, Science Direct, PubMed, and IEEE Xplore using the keyword sleep apps. In total, 1650 peer-reviewed articles were screened, and 51 were selected for inclusion. Sleep monitor was the most common functionality among the existing apps. Wearable devices such as smartwatches have always assisted sleep apps in collecting data. Facilitators and barriers to using apps were identified, along with the evidence-based design guidelines. Existing studies have proved the initial validation and efficiency of delivering sleep treatment by mobile apps; however, more research is needed to improve the performance of sleep apps and devise a way to utilise them as a therapy tool.